Structural history of ophiolite obduction, Bay of Islands, Newfoundland - SUHR, G; Cawood, Peter Anthony (1993)
Obduction-related structures in the ophiolitic Bay of Islands Complex, west Newfoundland, are classified into shearing dominated and accretion dominated. Mapping of these structures is combined with other geological constraints and provides the basis for a reconstruction of the obduction history of the ophiolite. The earliest detachment structures are shearing dominated and are preserved in the basal peridotites. They indicate north-directed thrusting. Detachment was facilitated by the shallow position of the lithosphere-asthenosphere boundary below the recently extinct Bay of Islands spreading ridge. Detachment involved lithosphere of the southern side and immediate northern side of the ridge. During the early stages of detachment, the Coastal Complex, an arc-related unit located to the west of the Bay of Islands Complex, acted largely as a lateral ramp to obduction. Early accretion occurred in two tectonic situations: (1) at the stage when the basal decollement plane intersected the boundary to the structurally and lithologically diverse Coastal Complex; this resulted in accretion of blocks up to several hundred meters thick with a lithological make-up not known from the Bay of Islands Complex; and (2) at the stage when the basal thrust plane intersected the oceanic crust. Deformation switched into the mafic and hydrated footwall lithologies and led to intermittent accretion of mafic oceanic crustal rocks now preserved in the metamorphic sole. Only the Lewis Hills massif, located close to the Coastal Complex during detachment, preserves evidence for both types of early accretion. At a later stage of obduction, localized removal of the basal sequence of the ophiolite was associated with accretion of a diverse assemblage of harzburgites, amphibolites, and greenschists.